2017
DOI: 10.18632/oncotarget.19594
|View full text |Cite
|
Sign up to set email alerts
|

Reversible regulation of ORC2 SUMOylation by PIAS4 and SENP2

Abstract: The small ubiquitin-related modifier (SUMO) system is essential for smooth progression of cell cycle at the G2/M phase. Many centromeric proteins are reversibly SUMOylated to ensure proper chromosome segregation at the mitosis. SUMOylation of centromeric Origin Recognition Complex subunit 2 (ORC2) at the G2/M phase is essential in maintaining genome integrity. However, how ORC2 SUMOylation is regulated remains largely unclear. Here we show that ORC2 SUMOylation is reversibly controlled by SUMO E3 ligase PIAS4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…It has been shown that ORC2 localizes to the centromeres during the cell cycle G2/M phase [43,54,55] (Figure 1a). Post-translational modification of ORC2 with the SUMO2 attachment is important for the maintenance of centromeric histone H3 methylation status, and the prevention of heterochromatin re-replication via the recruitment of demethylase KDM5A [8] (Figure 1b). Moreover, the regulation of ORC2 SUMOylation at the G2/M phase is critical for smooth progression of the mitotic cycle of cells.…”
Section: Heterochromatin Formation and Transcription Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that ORC2 localizes to the centromeres during the cell cycle G2/M phase [43,54,55] (Figure 1a). Post-translational modification of ORC2 with the SUMO2 attachment is important for the maintenance of centromeric histone H3 methylation status, and the prevention of heterochromatin re-replication via the recruitment of demethylase KDM5A [8] (Figure 1b). Moreover, the regulation of ORC2 SUMOylation at the G2/M phase is critical for smooth progression of the mitotic cycle of cells.…”
Section: Heterochromatin Formation and Transcription Regulationmentioning
confidence: 99%
“…In contrast, in metazoa, ORC has a more dynamic interaction with DNA. For example, the complex is not bound to the chromatin during the S and M phases in Xenopus [7] and human cells [8]. Interestingly, in Drosophila and human cells, the ORC1 subunit appears to be a key regulator of ORC replicative function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, SENP1 and SENP2 are closely connected and are involved in both SUMO maturation and deconjugation 11. Wang et al showed that SENP2 is a desumoylation protease that has a significant role in the modulation of transforming growth factor-β signaling 12. Based on these previous studies, we decided to investigate the relationship between the highly homologous SUMO family members and the progressive loss of aggrecan during OA progression, and whether SENPs are involved in OA.…”
Section: Introductionmentioning
confidence: 99%